2022
DOI: 10.4000/essais.10762
|View full text |Cite
|
Sign up to set email alerts
|

Le processus doctoral : entre souffrances et vulnérabilités

Abstract: L'aventure doctorale en Sciences Humaines et Sociales (même lorsqu'elle est menée dans le cadre d'un contrat doctoral unique), confronte à de multiples précarités. L'isolement et le manque de repères s'avèrent parfois si prégnants qu'ils empêchent les personnes vulnérabilisées d'en parler : pas de groupe de pairs, pas de rythmicité calendaire, pas de lieu de travail, etc. Or, le parcours doctoral est une expérience intense, qui mobilise, pendant plusieurs années de vie, des investissements conséquents (enseign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…According to this definition, qualitative studies on doctoral researchers' psychological distress have observed anxiety, depression, and constant concerns, sometimes accompanied by mental and physical fatigue (Cotterall, 2013;Cristia, 2022;Enzor, 2017). More specifically, anxiety experienced during the doctoral project has been characterized by worrying and fear of professional failure.…”
Section: Psychological Distressmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this definition, qualitative studies on doctoral researchers' psychological distress have observed anxiety, depression, and constant concerns, sometimes accompanied by mental and physical fatigue (Cotterall, 2013;Cristia, 2022;Enzor, 2017). More specifically, anxiety experienced during the doctoral project has been characterized by worrying and fear of professional failure.…”
Section: Psychological Distressmentioning
confidence: 99%
“…It is a professional position with diverse requirements. Doctoral researchers have a hybrid status, as they are neither completely students nor employees (Cristia, 2022). Furthermore, the pressure on them to perform, be productive, and reach perfection is at its peak (Hazell et al, 2020).…”
Section: Contextualizing Psychological Healthmentioning
confidence: 99%